The world of sugar: How the sweet stuff transformed our politics, health, and environmen over 2,000 years - Bosma, Ulbe (London Harvard University Press, 2023)
The definitive 2,500-year history of sugar and its human costs, from its little-known origins as a luxury good in Asia to worldwide environmental devastation and the obesity pandemic. For most of history, humans did without refined sugar. After all, it serves no necessary purpose in our diets, and extracting it from plants takes hard work and ingenuity. Granulated sugar was first produced in India around the sixth century BC, yet for almost 2,500 years afterward sugar remained marginal in the diets of most people.